SMALLHOLDER FARMERS’ ATTITUDE TOWARD QUALITY SEED OF IMPROVED COMMON BEAN VARIETIES IN TANZANIA - Kidudu, Joshua S.; Mwaseba, Dismas L.; Nchimbi-Msolla, Susan (International Journal of Research -GRANTHAALAYAH, 2019)
The importance of quality seed of improved varieties is well recognized and widely documented. However, smallholder farmers’ demand for quality seed of improved varieties has remained low for years. Previous studies have broadly identified technological, economic, institutional and human specific factors as major determinants of adoption. However, these studies tended to pay little attention on the influence of smallholder farmers’ attitude on decision to use quality seed of improved common bean varieties. Therefore, using cross-sectional research design, a survey was conducted in major regions producing common beans to determine smallholder farmers’ attitude towards quality seed of improved common bean varieties. Generally, smallholder farmers considered quality seed of improved common bean varieties to be beneficial (2.0616). However, they had moderate positive attitude towards qualities (1.4705) and accessibility (1.4598) of quality seed of improved common bean varieties. Nevertheless, they had very weak positive attitude toward availability (0.3068), promotion (0.3432) and marketability (0.3326) of their produce. Furthermore, findings indicated that benefits, qualities and marketability significantly influenced their attitude. These findings suggest that efforts to promote quality seed use have to concentrate on ensuring quality of claimed to be quality seeds and market outlets for produce from quality seed of improved common bean varieties.